Assay for detection of Trypanosoma cruzi antibodies in human sera based on reaction with synthetic peptides. - Vergara, U (1991)
Synthetic peptides modelled according to the amino acid sequences derived from the repeated domains of five Trypanosoma cruzi antigens were used in an immunoradiometric assay to detect antibodies appearing after natural human infections. An enzyme-linked immunosorbent assay and an indirect immunofluorescence assay performed with a complex antigenic mixture from parasites were used as controls. The results indicate that the synthetic peptides were recognized by a large proportion of serum samples collected from 34 patients with Chagas' disease in Chile and point to their possible use in diagnosis.